Penguatan Retorika Generasi Muda Kalimantan Tengah Melalui Kompetisi Pidato Berbasis Kearifan Lokal sebagai Strategi Pemberdayaan Budaya - Misnawati Misnawati; Yulina Mingvianita; Syarah Veniaty; Novela Hawini; Eko Patrio (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
This community service program aims to enhance the rhetorical skills of the youth in Central Kalimantan through a speech competition based on local wisdom. The program addresses the lack of platforms for developing culture-based communication, which is a major challenge in the community. This initiative aligns with Asta Cita 4 (Strengthening National Character and Culture) and Asta Cita 5 (Enhancing Human Resource Competitiveness), as well as supporting SDG 4 (Quality Education). Training was provided to 100 participants, who were taught through cultural documentation in the form of books and educational videos. Additionally, the program contributes to IKU 2 (Students Gaining Experience Outside Campus) and IKU 6 (Faculty Work Used by the Community) by producing academic publications such as scientific articles and ISBN books. The results of the program show a significant impact on improving participants' speaking skills, with a 41% increase in self-confidence, a 47% increase in understanding of local wisdom, and a 42% increase in speech abilities. Overall, the average improvement reached +43%, demonstrating the success of the program in enhancing participants' communication skills while preserving the culture of Central Kalimantan.